Pengaruh Fermentasi Limbah Rumput Laut Gracilaria sp. dengan Bacillus subtilis Terhadap Populasi Plankton Chlorophyceae [Effect Of Waste Seaweed Fermentation Of Gracilaria sp. With Bacillus subtilis Against On Plankton Populations Of Chlorophyceae] - Moch. Amin Alamsjah; Rani Frisca Christiana; Sri Subekti (Jurnal Ilmiah Perikanan dan Kelautan, 2011)
Abstract One of Indonesia's marine living resources is seaweed. There are about 18,000 species of seaweed around the world and 25 species of which have high economic value. In indonesia, there are 555 types of seaweed and four types of which are known as export commodities, that is Euchema sp., Gracilaria sp., Gelidium sp. and Sargasum sp. One type of algae is much cultivated in the waters of Indonesia is Gracilaria sp. Seaweed is widely cultivated because it has an important role in the effort to increase fish production and preservation of biological resources. However, sometimes the other result are found a lot of waste of seaweed in the field. Utilization of seaweed waste of Gracilaria sp. can be applied into organic fertilizer that is through a biological fermentation process using microbial proteolytic. The aims of the study to determine the effect of the waste seaweed fermentation of Gracilaria sp. with Bacillus subtilis on plankton populations of Chlorophyceae. The research was perform in August 2011 at the Laboratory of Fisheries Education, Faculty of Fisheries and Marine, University of Airlangga, Surabaya. The design of experiments in this study using Completely Randomized Design (CRD) with 6 treatments and 4 replications. The treatments were: (A) control, (B) 10ml/l of seaweed waste liquid without fermentation, (C) 5ml/l of seaweed waste liquid using fermentation, (D) 10ml/l of seaweed waste liquid using fermentation, (E) 15ml/l of seaweed waste liquid using fermentation, (F) 20ml/l of seaweed waste liquid using fermentation. The main parameter is plankton populations of Chlorophyceae, while supporting parameter water quality. Data analysis using analysis of variance (ANOVA), when there is a difference followed by Duncan's Multiple range test. The results showed that the utilization of waste seaweed of Gracilaria sp. Using fermentation with isolated bacterial of Bacillus subtilis produce significantly different population (p <0.05) and D the treatment that is 10ml/l of seaweed waste liquid using fermentation, showed the highest cell density of 264,252 cells / ml. Based on the results of Duncan's Multiple range test showed that the D treatment give the best effect among all of the treatments. Water quality parameters during the study remained within the tolerance limit for the growth of Chlorophyceae, pH 7-8 and the water temperature ranges between 2729o C.